Solving the Problem of Finding Hypothetically Connected Objects by Means of Spatial Multi-Valued Structures - Chetverikov, G.G.; Vechirska, I.D.; Leshchynskyi, V.A. (Штучний інтелект, 2011)
In the work the basic aspects of mathematical modeling of AFP-structures as universal functional converters
of spatial type on the basis of decomposition of multiple-valued structures are investigated, also there have
been investigated an approach to the implementation of the linear logical transformation finding method for
solving the problem of finding hypothetically connected subscribers in the automated system of
complex calculations of telecommunication enterprise. У роботі досліджено основні аспекти математичного моделювання АСП-структур як універсальних
функціональних перетворювачів просторового типу на основі декомпозиції багатозначних структур, а
також був розглянутий підхід впровадження лінійного логічного методу виявлення перетворення, щоб
вирішити гіпотетично зв’язану проблему передплатників в автоматизованій системі складних обчислень
телекомунікаційного підприємства. В работе исследованы основные аспекты математического моделирования АКП-структур как
универсальных функциональных преобразователей пространственного типа на основе декомпозиции
многозначных структур, а также был рассмотрен подход к выполнению линейного логического метода
обнаружения преобразования для того, чтобы решить гипотетически связанную проблему подписчиков в
автоматизированной системе сложных вычислений телекоммуникационного предприятия.